Tracer study of bachelor of science in entrepreneurship graduates of Kalinga State University - GRETCHEN CALAGUI DAWATON (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: This paper aimed to assess the practical applicability of Kalinga State University’s Bachelor of Science in Entrepreneurship curriculum to the graduates’ chosen fields of work or business. Methodology: The graduates’ responses were primarily gathered using a modified version of the Commission on Higher Education’s Graduate Tracer Study (GTS) questionnaire. Forty-four (44) grads from batch 2015-2019 filled out the google form questionnaire that was sent out via email and messenger. Microsoft Excel was used to calculate and analyze the numerical data collected via Google Forms. Findings: The results demonstrated that the skills, knowledge, and experiences gained by students at the University were applicable and beneficial to their current professions. However, few graduates opened their businesses after graduation because of a lack of funding for initial investment. However, most B.S. Entrepreneurship alums were unable to launch their own businesses are now gainfully em ployed at private companies. Furthermore, most recent college graduates who aren’t working are doing so for reasons unrelated to their education or family. The study found that alums had overwhelmingly positive impressions of the University’s teaching staff, student body, and overall infrastructure. Implications/Novel Contribution: Therefore, this paper’s findings will inform Kalinga State University’s efforts to enhance the B.S. Entrepreneurship curriculum, learning environment, facilities, and overall services for its students and other Higher Education institutions offering entrepreneurship education .